Raznolikost perspektiv v ameriškem realističnem mladinskem romanu - Mazi-Leskovar, Darja (Otrok in knjiga, 1999)
Young adult novel as a genre offers a great variety of perspectives, consequently there is nothing surprising in the fact that a diversity of points of view is not only a characteristic feature of the American realistic teenage novel, but also one of its most distinctive qualities. According to the definition of young adult novel which is intendent primarily for adolescent reading public and presenting the adequate age span protagonists, the predominant perspective is the point of view of an adolescent. Her or his perspective is above all influenced by her or his age, even if the environment she or he lives in, as well as the general cultural atmosphere in its broadest meaning exert considerable influence on young protagonist's view of the world. Thus it is logical that in the last decades of the 20th century, when young people have been given more and more attention also as far as socioeconomic role is concerned, the narrator is most often the main character. Moreover, even when the first-person narrator is replaced by the third-person narrator the perspective of the novel remains the one of the young protagonist. Consequently the social and emotional experience of the heroes is reflected in the attitudes presented, what gives a characteristic tone to the genre as a whole and differenciates it essentially from the nivels written for the adult reading public. The analysis of four American young adult novels, A Begonia for Miss Applebaum (Paul Zindel), A Ring of Endless Light (Madelaine L'Engle), Julie of the Wolves (Jean Craighead George), and Can You See Your Parents for Malpractice (Paula Danziger), has shown that one of the noticable features of the American realistic young adultnovel is the change of perspectives. The evolution of the main hero's point of view is primarily the consequence of her or his growing up, and it is illustrated above all by the awareness of the possibility to influence one's future and to attain one's goals. The point of view of the protagonists is therefore predominantly optimistic and the general perspective may be defined as the one of hope.
Keywords: mladinska književnost; young adult literature; American literature; ameriška književnost; mladinski roman